Implementation Of The Hybrid Multilayered Perceptron Network In Assembly Language. - Tan, Kuan Liung; Mashor, Mohd Yusoff; Ali, Ahmad Nazri; Mat Isa, Nor Ashidi (2004)

(untitled)
In this research, an approach to implement the Hybrid Multilayered Perceptron Network. (HMLP) in assembly language is discussed in detail.